The role of oxidizer on energy conversion of Al + MoO3 reactive material projectiles under ballistic impact - Charles L. Croessmann; Larry R. Queen; Cole.A. Ritchie; Pascal Dube; Michelle L. Pantoya (Materials & Design)
The goal of a reactive material (RM) projectile is to produce appreciable chemical potential energy on demand while additionally providing structural integrity for the application. Recent advances in diagnostics and analysis techniques present opportunities to examine energy partitioning from a RM projectile upon high velocity impact, fragmentation, and reaction. This study analyzes partitioning chemical energy into gas and condensed phase energies as a function of the solid oxidizer concentration within the RM projectile and the oxygen concentration in the gas environment. Projectiles were made by consolidating aluminum (Al) with varied concentrations of molybdenum trioxide (MoO3) powders, and ballistic impact experiments were performed in air and inert argon environments. The RM projectiles were launched at 1050 m/s into two different chambers. Pressure measurements were made in a semi-sealed calorimetric chamber to quantify gas phase energy conversion and thermography measurements were made using a visual chamber to quantify condensed phase energy conversion. The results show increasing MoO3 concentration promotes ignition, fragmentation, and more rapid gas energy conversion in an air environment. The opposite was observed in argon, increasing MoO3 concentration promotes condensed phase energy conversion. Processes responsible for controlling energy partitioning are discussed.